Factors influencing Turkish parents' intentions towards anti-consumption of junk food. Issue 1 (20th March 2019) - Yarimoglu, Emel; Kazancoglu, Ipek; Bulut, Zeki Atıl
Abstract : Purpose: The purpose of this paper is to analyze parents' intentions toward the anti-consumption of junk food for their children. The paper incorporated the theory of planned behavior (TPB) using two external factors, which previously have not been investigated together. Design/methodology/approach: A questionnaire was designed from previous studies consisting of the constructs of the TPB (intention, attitude, subjective norm, perceived behavioral control) and two external factors (anticipated regret and perceived risk). An online survey was conducted among 392 participants. Confirmatory factor analysis and structural equation modeling were used to test the hypotheses. Findings: All hypotheses were supported. Attitudes, subjective norms and perceived behavioral control affected parental intentions toward the anti-consumption of junk food. The two external factors of the model also affected parental intentions toward the anti-consumption of junk food. Research limitations/implications: There were four limitations regarding participants, the research model and product type. Practical implications: Junk food producers, sellers, fast food restaurants and public policies should encourage healthy lifestyles, particularly for children. Junk food producers and fast food restaurants should offer healthier nutritional options. Governmental policies should include legal regulations to restrict marketing strategies for unhealthy products. Parents, as the primary influencers of children, should be educated regarding the anti-consumption of junk food. Originality/value: The study contributed to the anti-consumption literature by analyzing buying intentions toward junk food within the concept of anti-consumption, analyzing intentions by adding anticipated regret and perceived risk to the TPB model and analyzing the effects of perceived risk on anticipated regret.